Strategi Pengendalian Alih Fungsi Lahan Pertanian Pangan di Kawasan Mamminasata Provinsi Sulawesi Selatan - Hairuddin Hairuddin; Muh. Fiqruddin; Rahmad Rahmad; 3Andi miftahuulum; Adnan Adnan (Fakultas Teknik Universitas Cenderawasih, 2024)
The conversion of food land functions in the Mamminasata Region of South Sulawesi Province, is always increasing due to urban growth, population development, emigration and the economy. This study aims to determine the strategy for controlling the conversion of agricultural land functions in order to implement Law No.41/2009 and Regional Regulation No. 4 tahun 2014 concerning the protection of sustainable agricultural land in the Mamminasata area of ​​South Sulawesi province. The type of research used is a combination of qualitative and quantitative methods. This research was conducted in the Mamminasata Region, South Sulawesi Province from October to December 2016. Primary data collection was obtained using landsat 7 ETM maps and Spot 4 imagery and interpretation. Secondary data was obtained from government stakeholder interviews, surveys and direct interviews with local communities systematically and based on research objectives, causal factors based on survey results, interviews from informants and the public are external factors, internal and policy factors, then thus to overcome these problems a sustainable food land control strategy must be carried out including: Strengthening farmer institutions and related agencies, Protection and empowerment of land-owning farmers, Utilizing and protecting sustainable food agricultural land, providing incentives and disincentives to land owners, sharecroppers , and farmer groups, optimizing sustainable food agriculture land: by means of intensification, extensification and diversification of agricultural land, imposing sanctions and penalties on those who violate regional regulations and RTRW, and following up RI Law No. 4 tahun 2014 and South Sulawesi provincial regional regulations no. 4 of 2014 to determine the zoning of sustainable food agricultural land in the Mamminasata area as one of the food storages in South Sulawesi.